Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica juncea L.) Tumpang Sari Tanaman Chaya (Cnidocolus aconitifolius) dengan Ukuran Tajuk Berbeda - Prayoga, Apri; Gustiar, Fitra; Marlina, Marlina; Budianta, Dedik; Ammar, M.; Susilawati, Susilawati (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Prayoga, A., Gustiar, F., Marlina, M., Budianta, D., Ammar, M., Susilawati, S. (2023). Growth and yield of mustard (Brassica juncea L.) intercropping chaya plants (Cnidocolus aconitifolius) with different canopy sizes. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 306-317). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Intercropping is planting pattern that cultivates more than one type of plant in a certain unit of time aimed at increasing productivity. This study was conducted to examine the size of the chaya plant crown and the density of mustard plants using an intercropping system in the area of chaya plants (Cnidoscolus aconitifolius) in order to obtain optimal production and growth results. This study was conducted using a split plot design with two factors. The first factor as the main plot of the cultivation system is 3 treatments, namely conventional / monoculture (K0), intercropping on chaya plants with a header diameter of 80 cm (K1), and intercropping on chaya plants with a crown diameter of 120 cm (K2). The second factor is the density or planting distance as a child plot with a planting distance of 15 x 15 cm (P1), and a planting distance of 15 x 20 cm (P2). The data that has been obtained is then analyzed by the Analysis of Variance (ANOVA) method using the R-Studio application. The results showed that the cultivation of mustard greens (B. juncea L.) tosakan variety with intercropping patterns on conventional obtained the best results. But the 80 cm chaya plant canopy is not significantly different from conventional planting patterns so it can be said that the 80 cm chaya canopy is better than the 120 cm chaya plant canopy. The optimal planting distance is a planting distance of 15 x 15 cm because it is not significantly different from a planting distance of 15 x 20 cm in terms of the quality of the results obtained. In terms of quantity, a planting distance of 15 x 15 cm will produce more production results than a planting distance of 15 x 20 cm. So it can be concluded that the cultivation of mustard greens (B. juncea L.) varieties of intercropping chaya plants (Cnidoscolus aconitifolius) can be done on the chaya crown 80 cm and with a planting distance of 15x15 cm.